2016
DOI: 10.1103/physrevb.93.161107
|View full text |Cite
|
Sign up to set email alerts
|

Broadband terahertz spectroscopy of the insulator-metal transition driven by coherent lattice deformation at theSmNiO3/LaAlO3interface

Abstract: We investigate the non-equilibrium insulator-metal transition driven in a SmNiO3 thin film by coherent optical excitation of the LaAlO3 substrate lattice. By probing the transient optical properties over a broad frequency range (100 -800 cm -1 ), we analyze both the time dependent metallic plasma and the infrared optical phonon line shapes. We show that the light-induced metallic phase in SmNiO3 has the same carrier density as the equilibrium metallic phase. We also report that the LaAlO3 substrate acts as a t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
(19 reference statements)
1
15
0
Order By: Relevance
“…Ultrafast resonant soft x-ray diffraction experiments have, for example, revealed that a supersonic paramagnetic/antiferromagnetic front accompanies the insulator metal transition (IMT), propagating from the hetero-interface into the material [8]. Additional insight was provided by optical experiments in a related LaAlO 3 /SmNiO 3 heterostructure, in which the same substrate excitation was shown to induce an IMT in the nickelate film also above the Néel temperature [9]. This observation was taken as evidence that melting of magnetic order may follow the IMT and may not be its cause.…”
Section: /16mentioning
confidence: 99%
“…Ultrafast resonant soft x-ray diffraction experiments have, for example, revealed that a supersonic paramagnetic/antiferromagnetic front accompanies the insulator metal transition (IMT), propagating from the hetero-interface into the material [8]. Additional insight was provided by optical experiments in a related LaAlO 3 /SmNiO 3 heterostructure, in which the same substrate excitation was shown to induce an IMT in the nickelate film also above the Néel temperature [9]. This observation was taken as evidence that melting of magnetic order may follow the IMT and may not be its cause.…”
Section: /16mentioning
confidence: 99%
“…Many other materials showing dynamic THz responses applicable to active THz modulation also exist, such as NbO 2 , [211] InSb, [212,213] QWs, [214] titanium oxides, [215] orthoferrites, [216][217][218] rare-earth nickelates, [219][220][221] manganites, [222][223][224] topological insulators, [225][226][227] multiferroics, [228] molecular crystals, [229,230] medicines, [231] polymers, [232][233][234][235][236][237][238] and halide perovskites, [239][240][241][242][243][244][245][246] to name but a few. Considering the diversity of the material properties and the control mechanisms, plasmonic hybridization may bring about new possibilities for a wide variety of active THz devices.…”
Section: Potential Candidatesmentioning
confidence: 99%
“…2,3 Laser-induced mechanisms provide another strategy to manipulate quantum phases in these materials. [4][5][6][7] In these experiments, phase transitions or transitions to metastable states are induced by a time-dependent perturbation. The resulting dynamics often follows a highly nonthermal trajectory and in the context of IMTs interesting questions arise concerning both the timescale and the pathway for the non-adiabatic switching.…”
Section: Introductionmentioning
confidence: 99%